COST AND TIME ANALYSIS USING THE EARNED VALUE METHOD IN THE CONSTRUCTION PROJECT OF THE BPBD BUILDING COMPLEX IN PASURUAN DISTRICT - Cahyono, Bagus; Marleno, Risma; Oetomo, Wateno (Transpublika Publisher, 2023)
In the construction project of the Pasuruan Regency BPBD building complex which is currently still running, there have been problems related to the schedule for the implementation of its activities. The problem in question is the delay in the schedule for the implementation of its activities. where the results of the progress realization are not in accordance with the schedule plan, through this paper an evaluation is carried out related to performance in the field through an approach using the Earned Value Method. The data analysis process is carried out by calculating analysis indicators including BCWS, BCWP and ACWP. The results of the performance evaluation of the Pasuruan Regency BPBD building complex construction project using the Earned Value method show that the project has a negative deviation in the activity implementation schedule. The cost performance indicator on this project shows a Cost Performance Index (CPI) value of 1.137, which means that the costs incurred are greater than planned. While the time performance indicator shows a Schedule Performance Index (SPI) value of 0.949, which means the project is delayed from the planned schedule.